Rice productivity in Myanmar: Assessment of the 2023 dry season - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
Key Findings We analyze paddy rice productivity and profitability data for the dry seasons of 2022 and 2023, based on the Myanmar Agriculture Performance Survey (MAPS) fielded in the period of June 26th to July 25th, 2023. The survey covered plots of 659 rice paddy producers. It is found that: • Prices of inputs used in paddy production – fertilizer, labor, mechanization – increased between these two growing seasons by between 13 and 21 percent, on average. On the other hand, paddy prices at the farm increased by 68 percent. • Real profits, with nominal prices corrected by the change in the cost of an average food basket, from paddy rice farming during the dry season of 2023 increased by 41 percent compared to the dry season of 2022. While nominal profits for paddy rice farmers increased by 70 percent over the last two seasons, price inflation has been high in the country and real profit increased therefore much less. • Rice farmers increased input expenditures on paddy production by 50 percent compared to last year. However, larger farmers invested more and doubled input expenditures, likely attracted by the increased profits in paddy farming. • Rice productivity at the national level during the dry season of 2023 on farmers’ largest rice plot was slightly larger (+1.2 percent) than in the previous dry season. Substantial declines are noted in the coastal areas (-29 percent) and the Dry Zone (-5 percent), possibly linked to impacts of cyclone Mocha. • Thirteen percent of all crop farmers reported to have been affected by the cyclone Mocha and 3 percent of the crop farmers indicated that they lost their whole dry season harvest. Almost half of the affected farmers reported that the next monsoon season would not proceed as normal, likely affecting the production of rice – and other crops – in those areas during the next monsoon season. Recommended Actions • As paddy prices have gone up significantly, rice prices have gone up substantially as well, making the costs of Myanmar’s staple food unaffordable for some consumers, especially for the most vulnerable ones. Expansion of safety nets, targeted or self-targeted to the poorest, would therefore be beneficial. • The cyclone Mocha has destroyed harvests of farmers in Rakhine and part of the Dry Zone. As effects of the devastation of the cyclone will continue to be felt during the monsoon of 2023, further assistance for farmers in these areas to recover from these effects is called for. STRATEGY SUPPORT PROGRAM RESEARCH NOTE 99 SEPTEMBER 2023